PEMBERDAYAAN IBU HAMIL MELALUI PROGRAM EDUGIZI SEBAGAI UPAYA PENCEGAHAN KURANG ENERGI KRONIS (KEK) - Harna, Harna; Prita Dhyani Swamilaksita; Mira Asmirajanti; Asti Puji Lestari; Siti Fatimah Zahra; Venicia Eflin; Andi Muh Asrul Irawan (Politeknik Negeri Sriwijaya, 2024)
This community service activity was conducted with a focus on enhancing nutritional education for pregnant women in Lumpang Village, Parung Panjang Subdistrict, Bogor Regency, with the aim of preventing Chronic Energy Deficiency (CED). The education was delivered through a pocketbook titled